Design and Characterization of Naphthalene Ionic Liquids - Fernández-Stefanuto, Verónica; Somoza, Alba; Corchero, Raquel; Tojo, Emilia; Soto, Ana (Frontiers in Chemistry, 2020)
Surfactants have a great number of applications. Among these chemicals, petroleum sulfonates have been widely used due to their effectiveness reducing interfacial tension. This is the case of sodium octylnaphthalene sulfonate which is a solid with a very low solubility in water. To overcome these drawbacks, this work aimed to synthesize new surface active ionic liquids based on a naphthalene sulfonate anion and traditional cations of these salts (imidazolium, pyrrolidinium and pyridinium). The new chemicals showed high thermal stability, ionic liquid nature, and a stronger surfactant character than the original naphthalene. Moreover, they were found to be water soluble which greatly facilitates their applications in the form of aqueous formulations. 1-Hexyl-3-methylimidazolium 4-(n-octyl)naphthalene-1-sulfonate showed the best capacity to reduce water-air and water-oil interfacial tension.